Smart Apps Creator 3 Interactive Multimedia Based on Stream to Improve Students' Scientific Literacy During the Covid-19 Pandemic - Leny Heliawati; Fenny Pebriani; Didit Ardianto (Yayasan Keluarga Guru Mandiri, 2022)
By applying a learning-based approach model Science, Technology, Religion, Engineering, Arts, Mathematics in online learning, this study intends to investigate Smart Apps Creator, an interactive multimedia application to promote students' scientific literacy. SAC interactive multimedia is used to learn the media and comprehend scientific concepts. Explaining problems, designing research, carrying them out, analyzing data, evaluating findings, and sharing knowledge are all aspects of scientific literacy. Through the use of this program, STREAM-based learning is being used to improve students' scientific literacy. The results of the students' pretest and posttest were used to collect and analyze the study data in the form of quantitative descriptive analysis. With 80 responses among the students who participated in the survey and five science teachers who had used STREAM-based interactive multimedia, the study tool was delivered to the target population via a WhatsApp group. The findings indicated that the average percentage of scientific literacy with N-Gain in the medium category was 68%, indicating an improvement in student learning as a result of the use of SAC interactive multimedia learning. The study's findings demonstrate that SAC-based STREAM interactive multimedia learning is statistically highly significant and has been demonstrated to be successful in raising students' levels of scientific literacy in online learning during the present epidemic.